TEACHERS’ AND STUDENTS’ PERCEPTIONS OF PROJECT- BASED LEARNING ACTIVITIES IN THE NEW TIENG ANH 6: A CASE STUDY = NHÌN NHẬN CỦA GIÁO VIÊN VÀ HỌC SINH VỀ HOẠT ĐỘNG DẠY HỌC THEO DỰ ÁN TRONG SÁCH GIÁO KHOA TIẾNG ANH LỚP 6 - Nghiem, Thu Tra (2020)
In the language teaching context, Project – based learning is praised as an effective method, from which both teachers and students can benefit. It is believed to develop students’ confidence and independence (Fried-Both 2002) as well as language skills (Levine 2004). Stoller (2006) also stated that PBL provides opportunities for natural integration of all four skills: reading, writing, listening and speaking. Therefore, using PBL method effectively is of great importance to teachers in general and to students in particular. Attempting to investigate the students’ and teachers’ perceptions of PBL activities at secondary level, the current research aimed to explore how the teachers and grade – six students at Me Tri secondary school had carried out the projects in the textbook. Besides, the study discovered the advantages they had that helped them conduct these projects. Also, it found out the difficulties they met while conducting these projects. Moreover, the benefits they perceive of when conducting these projects were also investigated.